Co-Designing Resilient Infrastructure: Participatory Approaches for Sustainable Implementation - MGBAJIAKA, JOHNBOSCO (Current Journal of Applied Science and Technology, 2025)
The infrastructure in many low-income neighbourhoods and marginalised populations is insufficient to meet their basic needs for economic mobility, safety, and health due to decades of underinvestment, social injustices, and systemic barriers. A structured participatory framework is presented in this paper to help plan and carry out resilient infrastructure projects in underprivileged communities across the United States. The main goal is to close the ongoing gap between technical engineering solutions and the particular social, cultural, and environmental needs of marginalised communities. The framework guarantees that infrastructure investments yield equitable, sustainable, and context-specific benefits by integrating local participation throughout the project lifecycle. The research framework incorporates concepts of collaborative design thinking, adaptive infrastructure management, and community-based participatory research (CBPR). It is organised around four main stages: (1) Community Needs Assessment; (2) Co-Design and Collaborative Planning; (3) Implementation and Monitoring; and (4) Evaluation and Scaling.  Stakeholder mapping, participatory workshops, geospatial modelling, and local oversight committees are some of the tools that are used to improve community engagement and accountability. The framework shows improved community buy-in, increased local capacity, and quantifiable resilience outcomes using a hypothetical neighborhood that is prone to flooding as a case study. The findings show that participatory approaches strengthen the social impact of engineering practice by bringing technical resilience objectives into line with national equity and environmental justice priorities. Outcomes include a 35% decrease in local flooding incidents and increased trust in municipal planning processes. By embracing this framework, practitioners and policymakers can promote resilient infrastructure investments that yield enduring, community-driven benefits, thereby achieving the overarching objective of creating sustainable, equitable, and adaptable communities in the United States.